(untitled) (MIST International Journal of Science and Technology, 2020)
At present, web applications are one of the most widely used software applications in different organizations. A website is a virtual representation of the structure of any organization. Good user experience of a website is highly dependent on the content organization or design of a website. Thus, the design is a very important factor to develop a high usability standard website. Different types of design techniques are used to develop different types of websites. It is a very challenging task to develop information-intensive websites using a suitable design technique so that the website can serve its intended purpose with enhanced usability and user experience. Therefore, the objective of this research is to compare the performance of two alternate design techniques for developing an information-intensive website. To achieve this objective, the existing design techniques were explored; and selected the Card Sorting and Interactive Dialogue Model (IDM) techniques to design two websites for an orphanage system. Later, the developed orphanage web systems were evaluated with ten participants through a user study; and found that the IDM design technique performs better than the Card Sorting technique in terms of the system’s usability and user experience. MIJST, Vol. 8(1), June 2020: 49-60